2009
DOI: 10.1007/s10803-009-0710-y
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Memories of Emotionally Charged Words in Autism Spectrum Disorder: Further Evidence for Atypical Emotion Processing Outside the Social Domain

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
2
18
0
1
Order By: Relevance
“…This interpretation fits well with the behavioral memory data, showing slightly higher FAs and lower sensitivity in the ASD group also indicating a difficulty in distinguishing studied from new unstudied items. Further support comes from previous research showing higher K rates in R/K recognition tests Bowler et al, 2007] and more intrusion errors in free recall tests [e.g., Bowler, Gardiner, Grice, & Saavalainen, 2000;Bowler et al, 2008;Kamio & Toichi, 2007;Tager-Flusberg, 1991] and work on memory illusions [Gaigg & Bowler, 2009]. Taken together, these results suggest some level of confabulation in ASD, which may be related to a problem with metacognition in terms of response monitoring.…”
Section: Discussionsupporting
confidence: 64%
“…This interpretation fits well with the behavioral memory data, showing slightly higher FAs and lower sensitivity in the ASD group also indicating a difficulty in distinguishing studied from new unstudied items. Further support comes from previous research showing higher K rates in R/K recognition tests Bowler et al, 2007] and more intrusion errors in free recall tests [e.g., Bowler, Gardiner, Grice, & Saavalainen, 2000;Bowler et al, 2008;Kamio & Toichi, 2007;Tager-Flusberg, 1991] and work on memory illusions [Gaigg & Bowler, 2009]. Taken together, these results suggest some level of confabulation in ASD, which may be related to a problem with metacognition in terms of response monitoring.…”
Section: Discussionsupporting
confidence: 64%
“…When further focusing on the intervention targets in verbal functions and in social perception or emotion processing and expression, multiple measures in both domains are needed. Atypicalities on behaviors closely related to both domains, including perception and production of prosody (see O’Connor 2012 for a review) and emotion processing on memory (Beversdorf et al 1998; Gaigg and Bowler 2008, 2009), should be focused on. Future investigations clarifying inconspicuous atypicalities or compensatory mechanisms in those domains will be useful in developing effective interventions for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Neither Budson et al nor El Sharkawy et al included positive lists. Neither did two other similar studies by Pesta, Murphy, and Sanders (2001) and Gaigg and Bowler (2009), in which case false memory for negative, arousing lists was compared to false memory for neutral lists. Brainerd, Stein, Silveira, Rohenkohl, and Reyna (2008), however, controlled arousal while manipulating valence, and found that positive and negative valence affected memory differently.…”
Section: Introductionmentioning
confidence: 93%